PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Andi Azwar Anas Idris; Adnan Hakim; Yusuf Yusuf (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
The objectives of the study are: 1) The effect of partial job satisfaction on organizational citizenship behavior (OCB) of teachers of SMAN 3 Bombana. 2) The effect of partial organizational commitment on organizational citizenship behavior (OCB) of teachers of SMAN 3 Bombana. 3) The effect of job satisfaction and organizational commitment simultaneously have effect on Organizational Citizenship Behavior (OCB) of the teachers of SMAN 3 Bombana.The research design used was quantitative research. The population of the study were all teachers of SMAN 3 bombana with the population of 40 persons, using saturation sampling. Data were retrieved by interviews and questionnaires. The data analysis technique was multiple regression model with the help of SPSS 24.The result of the study shows that: 1) Job satisfaction has positive and significant effects on teachers’ Organizational Citizenship Behavior (OCB). 2) Organizational commitment has positive and significant effects on teachers’ Organizational Citizenship Behavior (OCB). 3) Job satisfaction and organizational commitment simultaneously have positive and significant effects on Organizational Citizenship Behavior (OCB) of SMAN 3 bombana teachers.Keywords: job satisfaction, commitment, and organizational citizenship behaveior